(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In critical care settings, patients often face prolonged immobilization due to the severity of their conditions and the necessary interventions. However, research increasingly demonstrates the significant benefits of early mobilization for patients in intensive care units (ICUs). This article explores the importance of early mobilization in critical care, providing insights for both nurses and physiotherapists. It examines the physiological and psychological impact of immobility on ICU patients and highlights the potential complications associated with prolonged bed rest. Furthermore, the article discusses evidence-based strategies for early mobilization, including patient assessment, safety considerations, and multidisciplinary collaboration between nursing and physiotherapy teams. By promoting early mobilization practices in critical care, healthcare professionals can improve patient outcomes, reduce complications, and enhance overall quality of care.